Factors governing construction project delivery selection: A content analysis. Issue 8 (November 2015) - Qiang, Maoshan; Wen, Qi; Jiang, Hanchen; Yuan, Shangnan
Abstract: Comprehensively identifying factors governing project delivery system (PDS) selection is crucial for construction projects. This paper aims at constructing a holistic system of governing factors. Based on review of previous studies, project condition factors and performance objective factors were identified to construct the factor system. To explore the perspective divergences, content analyses on Chinese and developed countries' literature were performed. The emphasizing frequencies of factors were calculated. T tests were performed to compare the relative importance of factors. Principal component analysis was employed to identify key factors. The results show that three groups of factors, namely, internal project conditions, external project conditions and project performance objective factors are the main factors governing PDS selection. Some factors are of different importance in China and developed countries, mirroring the management maturity and philosophy gaps. The proposed factor system acts as a guidance to PDS selection and lays solid foundation for future studies. Highlights: We identify governing factors based on functioning mechanism analysis. This paper integrates conclusions of representative studies on PDS selection. This paper employs an extended content analysis method in empirical study. Perspective divergences exist in Chinese and developed countries' literature. The perspective gaps indicate management maturity and philosophy gaps.